Analysis of Financial Performance of the Jambi Province Forestry Service for the 2017-2021 - Alvionita, Nur Afni; Arum, Enggar Diah Puspa; Safelia, Nela (Indonesian Journal of Banking and Financial Technology, 2024)
Financial reports provide information about the financial position that is useful for most report users in order to make decisions and demonstrate accountability for the use of resources entrusted to users. The aim of this research is to determine the financial performance of the Jambi Province Forestry Service, analyzed from the Budget Realization Report for the 2017-2021 Fiscal Year. The method used is descriptive quantitative using economic ratios, effectiveness and efficiency. Data was obtained through field studies. The research results showed that the level of effectiveness in the Jambi Provincial Forestry Service for the 2017-2021 Fiscal Year was effective, for the economic level and overall budget efficiency it was quite efficient due to the use of the budget being too high.